2019
DOI: 10.1007/jhep10(2019)174
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear dynamics of the cold atom analog false vacuum

Abstract: We investigate the nonlinear dynamics of cold atom systems that can in principle serve as quantum simulators of false vacuum decay. The analog false vacuum manifests as a metastable vacuum state for the relative phase in a two-species Bose-Einstein condensate (BEC), induced by a driven periodic coupling between the two species. In the appropriate low energy limit, the evolution of the relative phase is approximately governed by a relativistic wave equation exhibiting true and false vacuum configurations. In pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 31 publications
1
37
0
Order By: Relevance
“…This case is similar to some of the examples in Ref. [18], where there was an effective cutoff from the size of the spatial grid used in the numerical simulations. We therefore have agreement between the two sets of results for this case.…”
Section: Numerical Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…This case is similar to some of the examples in Ref. [18], where there was an effective cutoff from the size of the spatial grid used in the numerical simulations. We therefore have agreement between the two sets of results for this case.…”
Section: Numerical Resultssupporting
confidence: 78%
“…However, Refs. [11,18] showed that the false vacuum state in this scheme can suffer from a parametric instability caused by the time-modulation of the system. The instability causes decay of the false vacuum state by a different mechanism than a first-order phase transition.…”
Section: Introductionmentioning
confidence: 99%
“…The analogy extends to the level of quantum field theory if the fluid is a coherent quantum system, like a Bose-Einstein condensate (BEC) near zero temperature. This opens the possibility of studying, in a laboratory setting, phenomena closely related to those of quantum field theory in curved spacetime, such as particle creation in an expanding universe and Hawking radiation from a black hole [1], the Unruh effect [2], and false vacuum decay [3].…”
Section: Introductionmentioning
confidence: 99%
“…in its "vacuum". Many proposals for simulating cosmological quantum field theory have been put forth as well [3,[8][9][10][11][12][13][14][15]. Experiments have not yet fully realized the analogy, but related phenomena have been observed.…”
Section: Introductionmentioning
confidence: 99%
“…Although the instanton approach borrows the wisdom of classically forbidden quantum penetration under the barrier, the physical picture behind the vacuum decay in field theory resembles the bubble nucleation in statistical physics [3,4] with quantum fluctuations replaced by thermodynamic fluctuations. Indeed, there is a cold atom analog of vacuum decay in field theory from experimental [5,6], theoretical [7], and simulational [8,9] perspectives. This inspires the request for vacuum decay in field theory via classically allowed channel, which is recently realized in lattice simulation [10] and formulated in real-time formalism [11].…”
Section: Introductionmentioning
confidence: 99%